RANCANG BANGUN CETAKAN PEMANEN (PERMANENT MOLD) UNTUK PEMBUATAN PULLEY ALUMINIUM - Firdaus, Firdaus (AUSTENIT, 2010)
Many efforts have been done to increase efficiencies and margin (without ignoring the quality) in casting industry. Most of the producer of non-ferrous pulleys in South Sumatra region are handled by small and medium scale industries using simple technology. Therefore the research is intended to improve the process of making pulleys as cast product by changing the mold of the process from green sand casting mold to permanent mold (steel mold). As the geometry of the pulley is not so complex and the permanent mold enable us to mass produce of the non-ferrous pulley casting at a certain time. This research is conducted by making the design of the mold and the produce the prototype of the permanent molding in such a way so that the molding can replace the green sand casting molding to produce the same product without decreasing the quality. Research results show that permanent mold could produce pulleys as cast product faster than using the green sand mold and in certain amount of the product can cut the production cost.